Savings Training for Elementary School Students in Sumberjaya Village, Kroya District, Indramayu Regency - Esha Safitri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Developing financial character from an early age is a strategic step in preparing a generation that is independent and disciplined in managing economic resources. However, elementary school students' understanding of the importance of financial management through saving is often limited to theoretical aspects without ongoing practice. This study aims to increase the interest and understanding of elementary school students in Sumberjaya Village regarding the importance of saving from an early age as a means of educating them about personal financial management. The method used in this program is a direct training approach through interactive socialization and practical pocket money management. The results of the activity indicate an increase in children's interest in setting aside a portion of their pocket money for savings, as well as a growing understanding of the benefits of saving in meeting future needs. The conclusion of this study confirms that participatory training is effective in developing positive habits and financial discipline in children, although more optimal timing is needed for its implementation.